Multi-causal determinants of anemia among women of reproductive age in Vietnam - Nguyen, Phuong Hong; Gonzalez-Casanova, Ines; Nguyen, Hieu; Pham, Hoa; Truong, Truong; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2014)
We examined the determinants of anemia using data obtained at baseline from 4986 women of reproductive age participating in a micronutrient supplementation trial in rural, North Vietnam. Hemoglobin (Hb) was measured from capillary blood samples using Hemocue. Plasma ferritin and retinol binding protein (RBP) were measured using the ELISA method. The prevalence of anemia (Hb<12 g/l), iron deficiency (Fe<12 µg/L), insufficient iron stores (Fe<30 µg/L) and iron deficiency anemia were 19.7%, 3.5%, 14.4% and 1.9%, respectively. The results using Structural Equation Modeling (SEM) techniques showed that ferritin concentration (0.29 per log‐mg/dl), number of children (‐0.19), and socioeconomic status (0.09) were directly associated with Hb concentration (p<0.05 for all). RBP was associated with Hb both directly (0.28 mg/dl) and indirectly (0.09 mg/dl) through ferritin (p<0.001), and hookworm infection was indirectly associated with Hb (‐0.11) through RBP and ferritin (p=0.025). Meat consumption, occupation, education, owning a hygienic toilet, and food insecurity however were not associated with Hb. Contrary to expectations, iron deficiency accounted for a very small proportion of anemia. These findings demonstrate the complex etiology of anemia and provide a useful framework that could be used to target and evaluate appropriate strategies for the prevention of anemia in similar settings and other populations.Supported by the Micronutrient Initiative and the Mathile Institute for the Advancement of Human Nutrition